IMPROVING OVEN MACHINE EFFECTIVENESS USING TOTAL PRODUCTIVE MAINTENANCE (TPM) APPROACH - Pangestu, Akbar Fitri Adi; Al-Faritsy, Ari Zaqi (Universitas Islam Nahdlatul Ulama Jepara, 2025)
One of the main tools used in bread production at the Azhari bakery is the oven machine. Common problems with the oven machine include leaks in the baking tray, a rusty firebox, and worn-out ignition regulators, resulting in downtime of 50 minutes. The purpose of this study is to identify the TPM pillars that must be implemented to improve the effectiveness of the oven machine. The methods used in this study include Overall Equipment Effectiveness (OEE), Six Big Losses analysis, Fishbone Diagram, determining TPM pillars based on the eight TPM pillars, and improvement plans using the 5W+1H method. Based on the OEE calculation, the average value is 100%, indicating that the OEE meets world-class standards. Based on the Six Big Losses analysis, the types of losses identified were Idling and Minor Stoppages and Reduced Speed Losses. In the fishbone diagram, there are three aspects influencing Idling and Minor Stoppages and Reduced Speed Losses: human aspects, machine aspects, and method aspects. To reduce losses in Idling and Minor Stoppages and Reduced Speed Losses, the Autonomous Maintenance (AM) pillar was implemented, consisting of routine basic maintenance of the oven machine, and Planned Maintenance (PM) by conducting scheduled maintenance on the oven machine. MENINGKATKAN EFEKTIVITAS MESIN OVEN MENGGUNAKAN PEDEKATAN TOTAL PRODUCTIVE MAINTENANCE (TPM)Salah satu alat utama pembuatan roti di pabrik roti bakar azhari adalah mesin oven, permasalahan yang sering terjadi pada mesin oven berupa kebocoran pada loyang, tungku api keropos, dan regulator pengapian aus dan mengalami downtime selama 50 menit. Tujuan penelitian untuk mengidentifikasi pilar TPM yang harus dilakukan dalam meningkatkan efektivitas mesin oven. Metode yang digunakan dalam penelitian ini adalah Overall Equipment Effectiveness (OEE), analisis Six Big Losses, Fishbone Diagram, menentukan pilar TPM berdasarkan delapan pilar TPM, dan rencana perbaikan menggunakan metode 5W+1H. Berdasarkan perhitungan OEE diperoleh rata - rata sebesar 100%, maka nilai OEE telah memenuhi standar world class. Berdasarkan analisis Six Big Losses terdapat jenis losses yaitu Idling and Minor Stoppages dan Reduced Speed Losses. Pada fishbone diagram terdapat 3 aspek yang mempengaruhi Idling and Minor Stoppages dan Reduced Speed Losses yaitu aspek manusia, aspek mesin, dan aspek metode. Untuk mengurangi losses pada Idling and Minor Stoppages dan Reduced Speed Losses, maka diterapkan pilar Autonomous Maintenance (AM) berupa kegiatan perawatan dasar mesin oven secara rutin dan Planned Maintenance (PM) dengan melakukan pemeliharaan yang terjadwal pada mesin oven.